2017
DOI: 10.1002/pros.23367
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the long non‐coding RNA FALEC promotes proliferation and migration of prostate cancer cell lines and predicts prognosis of PCa patients

Abstract: These findings suggested that FALEC may be a potential diagnostic and therapeutic target in patients with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…As various noncoding RNAs are transcribed from genomes, most studies focus on microRNAs and lncRNAs from transcribing genomes . Abnormal regulation of lncRNA has been found in some types of cancer, for instance, oral, gastric, and prostate cancers . Among these differentially expressed lncRNAs, a novel lncRNA, LINC00094, was discovered, which was obviously highly expressed in lung cancer tissues compared to normal tissues and could be a prognostic biomarker of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As various noncoding RNAs are transcribed from genomes, most studies focus on microRNAs and lncRNAs from transcribing genomes . Abnormal regulation of lncRNA has been found in some types of cancer, for instance, oral, gastric, and prostate cancers . Among these differentially expressed lncRNAs, a novel lncRNA, LINC00094, was discovered, which was obviously highly expressed in lung cancer tissues compared to normal tissues and could be a prognostic biomarker of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the classical interactive mode between HIF-1α and miRNAs, HIF-1α can also directly interact with the HREs in the lncRNA BC005927 promoter region, inducing lncRNA BC005927 to play its oncogenic role in gastric cancer by upregulating EPH receptor B4 (EPHB4) [81]. In addition, HIF-1α-mediated direct interactions regulate the expression of numerous lncRNAs, including lncRNA BX111 [82], lncRNA UCA1 [83,84], lncRNA FALEC [85], lncRNA MALAT1 [86], lncRNA ANRIL [87], and lncRNA NUTF2P3-001 [88], all of which play key roles in the development of tumors. Knowing of the existence of a direct interaction of HIF-1α and the HRE region existing in the lncRNA HOTAIR promoter in non-small-cell lung cancer [89], Bhan et al argued that synchronously with this interaction, MLL1 and CBP/p300 are recruited to the lncRNA HOTAIR promoter region, cooperating with HIF-1α to evoke the HOTAIR gene and promote tumorigenesis [90].…”
Section: Direct Regulation Of Hrl Transcription By Hif-1αmentioning
confidence: 99%
“…Although belonging to the lncRNA family, circRNAs are always discussed separately due to their unique structure gastric cancer upregulation transcriptional activation promotes invasion and metastasis [81] lncRNA BX111 pancreatic cancer upregulation transcriptional activation promotes EMT, proliferation, migration and invasion [82] lncRNA UCA1 osteosarcoma upregulation transcriptional activation promotes growth [83] lncRNA UCA1 bladder cancer upregulation transcriptional activation promotes proliferation, migration and invasion, inhibits apoptosis [84] lncRNA FALEC prostate cancer upregulation transcriptional activation promotes proliferation, migration and invasion [85] lncRNA MALAT1 HeLa and HEK-293T cells upregulation transcriptional activation N.A. [86] lncRNA ANRIL osteosarcoma upregulation transcriptional activation promotes invasion, inhibits apoptosis [87] lncRNA NUTF2P3-001 pancreatic cancer upregulation transcriptional activation promotes viability, proliferation and invasion [88] lncRNA HOTAIR lung cancer upregulation transcriptional activation promotes proliferation, migration and invasion [89] lncRNA HOTAIR pan-cancer upregulation transcriptional activation N.A.…”
Section: Regulation Of Circrnas By Hif-1αmentioning
confidence: 99%
“…Zhao et al., reported that FALEC expression is significantly increased in PCa tissue samples compared to adjacent normal tissue [ 19 ]. This study reported that knockdown of FALEC inhibited cell proliferation, migration and invasion in vitro .…”
Section: Lncrnas Associated With Prostate Cancermentioning
confidence: 99%